MANAJEMEN KOMUNIKASI PROGRAM KEGIATAN KOMUNITAS MUSIK TANAM KARYA DALAM MENYAMPAIKAN KRITIK SOSIAL - Febrianto, Rachmad; Dharmawan, Awang (Universitas Negeri Surabaya, 2024)
This research is based on the phenomenon of underground music in Indonesia, which, although a minority, influences social criticism through distinctive lyrics and musical styles. The aim of this study is to understand how Tanam Karya applies communication management strategies to voice social criticism. The research utilizes Communication Management Theory (POAC) as a conceptual framework, employing qualitative analysis methods including direct observation, in-depth interviews, and literature review. The findings indicate that Tanam Karya has successfully implemented effective communication management strategies. In the planning stage, they select relevant social issues such as injustice and environmental pollution. In organizing, they effectively manage resources and establish a structured organizational framework. During implementation, Tanam Karya utilizes social media and public activities to convey messages about social awareness and diversity. Systematic control and evaluation ensure that each event is assessed to rectify weaknesses and enhance efficiency.